High DHEAS in girls and metabolic features throughout pubertal maturation. (14th December 2021) - Pereira, Ana; Merino, Paulina M.; Santos, Jose L.; Iñiguez, German; Cutler, Gordon B.; Corvalan, Camila; Mericq, Veronica
Abstract: Context: An association between premature adrenarche and metabolic syndrome at presentation has been described. Our aim was to assess whether the presence of high dehydroepiandrosterone sulphate (DHEAS [HD]) at the adrenarche determines the risk of metabolic syndrome during puberty, taking into account body mass index (BMI) and birth weight. Design: Prospective observational. Patients: Five hundred four girls from the Growth and Obesity Chilean Cohort Study were followed from birth through puberty. At age ~7, subjects were classified by DHEAS concentrations into the HD (>75th percentile) or normal DHEAS (ND,  ≤75th percentile) subgroups. Measurements: Anthropometrics, semiannual clinical pubertal staging and hormonal and metabolic levels. The relationships among DHEAS at age ~7, metabolic syndrome, and each of its components independently, were analyzed by linear and logistic regression models during puberty and 1‐year postmenarche, adjusted by confounders. Results: Girls with HD at 7 years exhibited higher BMI, more central fat and higher serum androgen and insulin like growth factor (IGF)‐I levels throughout puberty. Also, girls with HD had a greater prevalence of hyperglycemia at B2 and B4 breast stages, and of low HDL at B4. At 1 year after menarche, HD girls had a higher prevalence of metabolic syndrome, and those with BMI > 1 SD score had a higher metabolic score and insulin levels than ND girls with similar BMI. Conclusions: Our observations suggest that girls with HD at the age of adrenarche may be at greater risk for metabolic syndrome at adolescence, especially in those who are overweight or obese. Our results emphasize the importance of lifestyle interventions for childhood overweight and obesity among girls with HD.